Chatbot empresarial para atención a clientes de la Universidad José Carlos Mariátegui, 2019-II: Business chatbot for customer service at José Carlos Mariátegui University, 2019-II - Jimenez Flores, Víctor Juan (2020)
The goal, reason for the research presented, was to describe and correlate the usability of a business chatbot and the attention to students of the José Carlos Mariátegui Filial Tacna University, 2019-II. In the method, quantitative research was used; and, the design, correlational, having a population of six hundred and fifty of both sexes, whose sample was two hundred forty two and a margin of error of 5%. The instruments used were System Usability Scale (SUS), to measure the usability of the business chatbot; and Service Performance (SERVPERF), for the quality of the perceived customer service by undergraduate and graduate students. The results show the existence of a significant correlation of 0.709 at a high level between the business chatbot and customer service. And, as a conclusion, there is a direct correlation of 0.709 in the high category among the research variables, and therefore, a business chatbot is closely related to customer service.